Effect of ultrasound in crude glicerol as pretreatment for methane production - Zschach, Lis Geraldine (2019)
As global energy supply is based on petroleum derivate, scarcity of natural sources and environmental concerns are problems associated to the energy supply as well as the increasing demand. Renewable energy sources can replace this conventional energy source and decrease the environmental emissions.. In this work is going to be evaluated the effect of ultrasound pretreatment on crude glycerol from biodiesel production process to improve the methane production from biogas in an anaerobic digestion process. Different times of pretreatment are going to be examined 10, 15 and 30 minutes to determinate the best performance and compare it to the untreated substrate. The results showed that ultrasound pretreatment improved methane production by using 30 minutes of treatment on crude glycerol.